Evaluating the Antioxidant Properties of the Ancient-Crop Tef (Eragrostis tef) Grain Extracts in THP-1 Monocytes - Christopher J. Cotter; Allison J. Wright; Anastasia V. Romanov; Tyler N. Graf; Eric D. Whisnant; Laura Flores-Bocanegra; Megan S. Doldron; Nicholas H. Oberlies; Zhenquan Jia; Ayalew Ligaba-Osena (Antioxidants, 2023)
Tef (Eragrostis tef) is an orphan crop that is widely grown in East Africa, primarily in Ethiopia as a staple crop. It is becoming popular in the Western world owing to its nutritious and gluten-free grains and the forage quality of its biomass. Tef is also considered to have a high antioxidant capacity based on cell-free studies. However, the antioxidant activity of tef has never been validated using a physiologically relevant cell model. The purpose of this study was to investigate the antioxidant capacity of tef grain extracts using a mammalian cell model. We hypothesized that the tef grain extracts are capable of modulating the cellular antioxidant response via the modulation of glutathione (GSH) biosynthetic pathways. Therefore, we evaluated the antioxidant activity of purified tef grain extracts in the human acute monocytic leukemia (THP-1) cell line. Our findings revealed that the organic fraction of grain extracts increased the cellular GSH level, which was more evident for brown-colored tef than the ivory variety. Moreover, a brown-tef fraction increased the expressions of GSH-pathway genes, including γ-glutamate cysteine ligase catalytic (GCLC) and modifier (GCLM) subunits and glutathione reductase (GR), an enzyme that plays a key role in GSH biosynthesis, suggesting that tef extracts may modulate GSH metabolism. Several compounds were uniquely identified via mass spectrometry (MS) in GSH-modulating brown-tef samples, including 4-oxo-β-apo-13-carotenone, γ-linolenic acid (methyl ester), 4,4′-(2,3-dimethyl-1,4-butanediyl)bis-phenol (also referred to as 8,8′-lignan-4,4′-diol), and (3β)-3-[[2-[4-(Acetylamino)phenoxy]acetyl]oxy]olean-12-en-28-oic acid. Tef possesses antioxidant activity due to the presence of phytochemicals that can act as direct antioxidants, as well as modulators of antioxidant-response genes, indicating its potential role in alleviating diseases triggered by oxidative stresses. To the best of our knowledge, this is the first report revealing the antioxidant ability of tef extracts in a physiologically relevant human cell model.